1995
DOI: 10.1023/a:1016263926946
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: IDE is the major enzyme which degrades insulin in enterocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Western BlottingsThe cytosolic fractions from rat and human intestines and Caco-2 cells were prepared, and Western blots were performed as published previously. 16,18,19 Results and Discussion IDE is present in rat hepatocytes, so the rat liver was used as a positive control. As shown in Figure 1, the immunostain- ing of IDE was heterogeneous throughout central and portal vein regions, weaker in the central regions (C), but more intense in the portal regions (P).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western BlottingsThe cytosolic fractions from rat and human intestines and Caco-2 cells were prepared, and Western blots were performed as published previously. 16,18,19 Results and Discussion IDE is present in rat hepatocytes, so the rat liver was used as a positive control. As shown in Figure 1, the immunostain- ing of IDE was heterogeneous throughout central and portal vein regions, weaker in the central regions (C), but more intense in the portal regions (P).…”
Section: Methodsmentioning
confidence: 99%
“…Because insulin is reportedly transported transcellularly through the intestinal epithelium of rats, 14,15 the importance of intracellular metabolism in limiting the oral absorption of insulin can not be over-emphasized. Previous studies from our laboratory have shown that the majority of insulindegrading activity (IDA) is from the cytosolic fractions of rat 16,17 and human 18 enterocytes and human adenocarcinoma (Caco-2) cells. 19 The cytosolic IDA of these cells all exhibit a K m in the range 14-92 nM, which is comparable to that of IDE.…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting to outline that if we compare these parameters with those obtained for the amyloid peptides Aβ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and Aβ [16][17][18][19][20][21][22][23][24][25][26][27][28] several similarities and some differences emerge [54]. In particular, the overall proteolytic activity toward the main cleavage sites (i.e., Phe 24 [16][17][18][19][20][21][22][23][24][25][26][27][28] ) is somewhat higher in the case of the B20-30 peptide due to a slightly more efficient cleavage rate-limiting step (see Table 2), whereas the substrate affinity of B20-30 appears intermediate between that of Aβ [1][2][3]…”
Section: Effect Of Metal Ions On B(20-30) Processing By Idementioning
confidence: 99%
“…Insulin degradation plays a major role in controlling insulin activity and most evidence supports IDE (insulin-degrading enzyme) as the primary degradative agent [1,2]. IDE is a zinc metalloprotease containing an unusual inverse zinc-binding site, HxxEH, that is involved in catalysis [3].…”
Section: Introductionmentioning
confidence: 99%
“…30 Inhibitors of insulin-degrading enzyme include 1,10 phenanthroline, p-choromeribenzoate, 31 and bacitracin. 32 Ziv et al 33 reported the use of a combination of an enhancer, sodium cholate, and a protease inhibitor to achieve a 10% increase in rat intestinal insulin absorption.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%